NETQUANT2: automated web-based quantification of neutrophil extracellular traps from fluorescence microscopy - Kumra Ahnlide, Johannes; Thelaus, Louise; Kahn, Fredrik; van Breda, Shane; Nordenfelt, Pontus (Frontiers in Immunology, 2024)
Neutrophil extracellular traps (NETs) are structures that neutrophils form in response to various stimuli, including invading pathogens. NETs are increasingly studied, and their importance has been demonstrated in autoimmunity and infection. However, no consensus has emerged on their quantification, with many studies resorting to manually counting NETs in microscopy images. NETQUANT is a free software for the automated quantification of neutrophil extracellular traps in fluorescence microscopy images. By employing automated image analysis based on biologically relevant criteria for defining NETs, NETQUANT eliminates user bias and reduces analysis time. Despite these advantages, NETQUANT has not reached widespread adoption, partly due to its dependence on proprietary software and challenges associated with local program setup, which has hindered its appeal. Here, we present NETQUANT2, an improved version based on the principles of NETQUANT, released as a web-based software for fast, simple, and unbiased NET quantification from microscopy images. The software guides researchers by displaying relevant morphological data from their sample and allows researchers to interactively configure the analysis, immediately seeing the impact on the result. NETQUANT2 further improves NETQUANT by enabling easy sharing and reusing of configurations and results and enhanced configuration options to handle complex samples better. We believe that the improved accessibility of NETQUANT2 will lead to better reproducibility in NET research and open the field to more researchers while keeping the quality of analysis high.